Nanoparticles as Alternatives for the Control of Haemonchus contortus: A Systematic Approach to Unveil New Anti-haemonchiasis Agents - Ali, Rehman; Ahmad, Nisar; Mussarat, Sakina; Majid, Abdul; Alnomasy, Sultan F.; Khan, Shahid Niaz (Frontiers in Veterinary Science, 2021)
Haemonchus contortus is an infectious gastrointestinal nematode parasite of small ruminants. This study addresses the in vitro/in vivo anti-haemonchiasis potential, toxicological effects, and mechanism of action of nanoparticles. Online databases were used to search and retrieve the published literature (2000 to 2021). A total of 18 articles were selected and reviewed, out of which thirteen (72.2%) studies reported in vitro, nine (50.0%) in vivo, and four (22.2%) both in vitro/in vivo efficacy of different nanoparticles. Mostly, organic nanoparticles (77.7%) were used including polymeric (85.7%) and lipid nanoparticles (14.3%). The highest efficacy, in vitro, of 100% was resulted by using encapsulated bromelain against eggs, larvae, and adult worm mortality at 4, 2, and 1mg/ml, respectively. While in vivo, encapsulated Eucalyptus staigeriana oil reduced worm burden by 83.75% and encapsulated Cymbopogon citratus nano-emulsion by 83.1%. Encapsulated bromelain, encapsulated Eucalyptus staigeriana oil, and encapsulated Cymbopogon citratus nano-emulsion were safe and non-toxic in vivo. Encapsulated bromelain damaged the cuticle, caused paralysis, and death. Nanoparticles could be a potential source for developing novel anthelmintic drugs to overcome the emerging issue of anthelmintic resistance in H. contortus. Studies on molecular effects, toxicological consequences, and different pharmacological targets of nanoparticles are required in future research.